Teaching guide - Munn, Kara (Clayton South Victoria: Blake Education, 2006)
A teaching resource to help get the best out of the Gigglers Gold set of chapter books suitable for ages 8.5+. Provides guided reading discussion points, four work sheets per book that integrate grammar, word study, comprehension, text types, fun activities and other extra activities that link to other key learning areas.
Kids